Dynamic simulation modelling of reversible solid oxide fuel cells for energy storage purpose. (1st December 2022) - Calise, F.; Cappiello, F.L.; Cimmino, L.; Vicidomini, M.
Abstract: The necessary integration of renewable based technologies in the current energy systems is leading to a faster development of energy storage technologies. As widely known, renewables suffer for unpredictability, and their massive utilization is significantly affecting grid stability and management. In this framework, the development of efficient and large electrical storage systems is becoming a pivotal point to achieve a stable electrical network based on renewables. This paper proposes a novel approach to reduce the energy excesses exported to the grid by a residential user equipped with a100 kW solar photovoltaic field. In particular, the electricity is stored as hydrogen by means of a 50 kW reversible solid oxide fuel cell. A comprehensive energy and economic simulation model of the system is proposed. In particular, a model of the reversible solid oxide fuel cell is developed in MatLab® and then integrated in TRNSYS17 for dynamic simulation purpose. Results showed that using the plant waste heat is crucial for improving fuel cell efficiency and plant energy performance. The proposed system achieves a reduction of the primary energy consumption by 74%. However, the proposed plant exhibits a poor economic profitability, with a payback period of 15 years. Highlights: Novel paradigm for residential electric energy storage based on hydrogen technology. Hydrogen as electric energy storage system is able to shave the peak of power demand and production. Very profitable energy and environmental results are achieved. The high capital cost of hydrogen related technologies limits the economic profitably of such plants.